TANK: THE PROGRESS OF A MONSTROUS WAR MACHINE - Liebenberg, Ian (Scientia Militaria - South African Journal of Military Studies, 2014)
The tank is viewed as the concrete manifestation of speed, mobility, all-round protection and firepower on the modern battlefield. Since its first operational deployment, it has received detailed and in-depth attention in terms of design, armament and upgrades, as well as strategy and tactics, including the evolution of armour strategy, doctrine and tactics on the battlefield. The tank redesigned battle space and has become a permanent fixture of conventional warfare over the past century.